Habitat traits and species interactions differentially affect abundance and body size in pond‐breeding amphibians. (16th March 2015) - Ousterhout, Brittany H.; Anderson, Thomas L.; Drake, Dana L.; Peterman, William E.; Semlitsch, Raymond D.; Colli, Guarino
Summary In recent studies, habitat traits have emerged as stronger predictors of species occupancy, abundance, richness and diversity than competition. However, in many cases, it remains unclear whether habitat also mediates processes more subtle than competitive exclusion, such as growth, or whether intra‐ and interspecific interactions among individuals of different species may be better predictors of size. To test whether habitat traits are a stronger predictor of abundance and body size than intra‐ and interspecific interactions, we measured the density and body size of three species of larval salamanders in 192 ponds across a landscape. We found that the density of larvae was best predicted by models that included habitat features, while models incorporating interactions among individuals of different species best explained the body size of larvae. Additionally, we found a positive relationship between focal species density and congener density, while focal species body size was negatively related to congener density. We posit that salamander larvae may not experience competitive exclusion and thus reduced densities, but instead compensate for increased competition behaviourally (e.g. reduced foraging), resulting in decreased growth. The discrepancy between larval density and body size, a strong predictor of fitness in this system, also highlights a potential shortcoming in using density or abundance as a metric of habitat quality or population health.